High-speed optical channel measurement system - O'Brien, D; Khoo, S; Zhang, W; Faulkner, G; Edwards, D (2001)
Diffuse and quasi-diffuse optical wireless systems have the potential to offer wireless coverage that is robust to any particular path between transmitter and receiver being blocked. The disadvantages of such systems are that links suffer from high path loss and multipath dispersion. Prediction of the magnitudes of these effects is crucial to the design of such systems, and simulation of these effects has been studied extensively. Measurements of the channel characteristics are also required, in order to verify the simulation results, and allow key effects to be identified. In this paper we describe a measurement system with the potential to provide link loss and frequency response of optical channels up to 1 GHz. The system uses a narrow field of view receiver that is scanned through a complete range of angles, so that complete angular resolution of the multipaths is achieved. The paper details system design and configuration, data processing and preliminary results up to a bandwidth of 200MHz.